2015
DOI: 10.1371/journal.pone.0119215
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Plasmodium falciparum K13-Propeller in Angola and Mozambique after the Introduction of the ACTs

Abstract: We report the presence of SNPs in Plasmodium falciparum K13-propeller gene in two African countries, Angola and Mozambique, where malaria is a serious public health problem. Samples were collected before and after ACT introduction as first-line treatment. In each country 50 samples collected before and 50 after ACT introduction were analysed. A total of three different mutations (R471R and R575R in Angola and V494I in Mozambique) were identified in five samples, all collected after the introduction of ACT. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 12 publications
(32 reference statements)
10
30
1
Order By: Relevance
“…This mutation is different from those previously identified in southeast Asia or Africa. 4,8,18,19 In contrast to our study, Kamau and others 7 reported the absence of any single nucleotide polymorphism (SNP) on isolates from central Ethiopia. Predicted protein structure of the R622I mutant kelch 13 propeller gene indicates that the mutation is likely to disrupt the function of the protein ( Figure 1B).…”
contrasting
confidence: 99%
“…This mutation is different from those previously identified in southeast Asia or Africa. 4,8,18,19 In contrast to our study, Kamau and others 7 reported the absence of any single nucleotide polymorphism (SNP) on isolates from central Ethiopia. Predicted protein structure of the R622I mutant kelch 13 propeller gene indicates that the mutation is likely to disrupt the function of the protein ( Figure 1B).…”
contrasting
confidence: 99%
“…In Africa, highly diverse and low-frequent K13 mutant alleles have been observed, with no evidence of selection, and none of these were associated with clinical artemisinin resistance assessed by the presence of parasites on day 3 following artesunate monotherapy or a 3-d ACT course. It is thought that artemisinin resistance has not been established in Africa, supported by the additional absence of evidence of invasion by Asian K13 alleles validated as molecular marker of artemisinin resistance (C580Y, R539T, I543T, Y493H), confirming previous smaller-sized studies (Conrad et al 2014;Torrentino-Madamet et al 2014;Cooper et al 2015;Escobar et al 2015;Hawkes et al 2015;Isozumi et al 2015;Kamau et al 2015;Taylor et al 2015). Haplotyping studies on the most common African mutant 578A !…”
Section: -800 Nmsupporting
confidence: 78%
“…The results confirmed the importance of the Y493H, R539T, I543T, and C580Y mutations in mediating in vitro artemisinin resistance (9). Although the four mutations are widely present in Southeast Asia, they are not observed in Africa (10)(11)(12)(13)(14). However, the P553L mutation, which is associated with delayed parasite clearance in Southeast Asia, was detected in Kenya and Malawi (12).…”
supporting
confidence: 65%